Cryptosporidium proliferans n. sp. (Apicomplexa: Cryptosporidiidae): Molecular and Biological Evidence of Cryptic Species within Gastric Cryptosporidium of Mammals - Kváč, Martin; Havrdová, Nikola; Hlásková, Lenka; Daňková, Tereza; Kanděra, Jiří; Ježková, Jana; Vítovec, Jiří; Sak, Bohumil; Ortega, Ynes; Xiao, Lihua; Modrý, David; Chelladurai, Jeba Rose Jennifer Jesudoss; et al. (PloS one, 2016)
The morphological, biological, and molecular characteristics of Cryptosporidium muris strain TS03 are described, and the species name Cryptosporidium proliferans n. sp. is proposed. Cryptosporidium proliferans obtained from a naturally infected East African mole rat (Tachyoryctes splendens) in Kenya was propagated under laboratory conditions in rodents (SCID mice and southern multimammate mice, Mastomys coucha) and used in experiments to examine oocyst morphology and transmission. DNA from the propagated C. proliferans isolate, and C. proliferans DNA isolated from the feces of an African buffalo (Syncerus caffer) in Central African Republic, a donkey (Equus africanus) in Algeria, and a domestic horse (Equus caballus) in the Czech Republic were used for phylogenetic analyses. Oocysts of C. proliferans are morphologically distinguishable from C. parvum and C. muris HZ206, measuring 6.8-8.8 (mean = 7.7 μm) × 4.8-6.2 μm (mean = 5.3) with a length to width ratio of 1.48 (n = 100). Experimental studies using an isolate originated from T. splendens have shown that the course of C. proliferans infection in rodent hosts differs from that of C. muris and C. andersoni. The prepatent period of 18-21 days post infection (DPI) for C. proliferans in southern multimammate mice (Mastomys coucha) was similar to that of C. andersoni and longer than the 6-8 DPI prepatent period for C. muris RN66 and HZ206 in the same host. Histopatologicaly, stomach glands of southern multimammate mice infected with C. proliferans were markedly dilated and filled with necrotic material, mucus, and numerous Cryptosporidium developmental stages. Epithelial cells of infected glands were atrophic, exhibited cuboidal or squamous metaplasia, and significantly proliferated into the lumen of the stomach, forming papillary structures. The epithelial height and stomach weight were six-fold greater than in non-infected controls. Phylogenetic analyses based on small subunit rRNA, Cryptosporidium oocyst wall protein, thrombospondin-related adhesive protein of Cryptosporidium-1, heat shock protein 70, actin, heat shock protein 90 (MS2), MS1, MS3, and M16 gene sequences revealed that C. proliferans is genetically distinct from C. muris and other previously described Cryptosporidium species.
Keywords: oocysty; Cryptosporidiosis; Phylogeny; Mice, SCID; Oocysts; Mole Rats; myši; zvířata; mikroftalmičtí podzemní hlodavci; fylogeneze; Mice; Animals; kryptosporidióza; myši SCID; Cryptosporidium